2007
DOI: 10.1161/circulationaha.106.643544
|View full text |Cite
|
Sign up to set email alerts
|

Nonfatal Acute Myocardial Infarction in Costa Rica

Abstract: Background-Cardiovascular disease, including myocardial infarction (MI), is increasing in developing countries.Knowledge of risk factors and their impact on the population could offer insights into primary prevention. For instance, 95% obtained Ն7% of energy from saturated fat, 25% had Յ5% of energy from polyunsaturated fat, 63% had Ն1% energy from trans fat, and 53% had low fiber intake (Ͻ25 g/d). Conclusions-These findings confirm the benefit of a healthy diet, physical activity, moderate alcohol, and cessat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 35 publications
(44 reference statements)
1
13
0
1
Order By: Relevance
“…In this population of Hispanic/Latino adults living in Costa Rica, we found that poor predictive lifestyle behaviors were associated with higher odds of MI, in line with previous studies 7, 9, 11, 36, 37, 38. The association for the GRS and higher odds of MI was consistent with previous literature analyzing SNPs in the chromosome 9p21 and higher risk of CHD and mortality 6, 10, 12.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In this population of Hispanic/Latino adults living in Costa Rica, we found that poor predictive lifestyle behaviors were associated with higher odds of MI, in line with previous studies 7, 9, 11, 36, 37, 38. The association for the GRS and higher odds of MI was consistent with previous literature analyzing SNPs in the chromosome 9p21 and higher risk of CHD and mortality 6, 10, 12.…”
Section: Discussionsupporting
confidence: 92%
“…A similar gradient of population‐attributable risk of only lifestyle factors was shown in a case–control study (15 152 cases and 14 820 controls) of acute MI in 52 countries, where the strongest risk factors for MI were smoking (population‐attributable risk=36%), abdominal obesity (20.1%), daily fruit and vegetables (13.7%), physical activity (12.2%), and regular alcohol consumption (7.1%) 37. In line with these results, strong evidence support that the modification of lifestyle factors could potentially decrease the risk of CHD, MI, stroke, and related clinical risk factors7, 9, 11, 36, 42, 43 even in secondary prevention 38…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations